Dimensi Metrik pada Graf Theta - Rahmadi, Deddy; Albar, Wakhid Fitri (JURNAL DIFERENSIAL, 2025)
Let $ G = (V, E) $ be a connected graph with vertex set $ V(G) $ and edge set $ E(G) $. For any two vertices $ u $ and $ v $ in $ G $, the shortest path distance between $ u $ and $v$ is denoted by $d(u, v)$. If $W = \{w_1, w_2, …, w_k\}$ is an ordered set of vertices in the connected graph $G$ , and $v \in V(G)$, then the representation of vertex $v$ with respect to $W$ , denoted as $r(v|W)$, is $r(v|W) = (d(v, w_1), d(v, w_2), …, d(v, w_k))$. If $r(v|W)$ is distinct for each vertex $v \in V(G)$, then $W$ is referred to as a resolving set for $G$. The resolving set with the smallest cardinality is called the minimum resolving set, and the cardinality of this set is the metric dimension of $G$, denoted by $\dim(G)$. This paper explores the metric dimension of the theta graphs.